1990
DOI: 10.2176/nmc.30.188
|View full text |Cite
|
Sign up to set email alerts
|

<I>Brain Metastasis from Transitional Cell Carcinoma of the Bladder</I>

Abstract: A rare case of brain metastasis from a transitional cell carcinoma (TCC) of the bladder is presented. A 66-year-old female underwent total removal of a bladder carcinoma and postoperative radiation therapy and chemotherapy.Right hemiparesis and seizures developed about 16 months later, and a solitary brain metastasis was discovered in the left Rolandic area. The tumor was totally removed and microscopic examination showed it to be TCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Bladder cancer is commonly a disease of older age and is a common malignant disease of the urinary tract [1-4]. The Korea National Statistical Office reported that an estimated 3,230 new cases of bladder cancer occurred in 2008 in Korea with 1,007 deaths.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bladder cancer is commonly a disease of older age and is a common malignant disease of the urinary tract [1-4]. The Korea National Statistical Office reported that an estimated 3,230 new cases of bladder cancer occurred in 2008 in Korea with 1,007 deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Babaian et al [5] reported that evidence of metastatic disease was found in a postmortem examination in approximately two thirds of patients with bladder cancer. The incidence of clinically detected distant metastases from urothelial carcinoma of the bladder reportedly ranges from 9.5% to 29% [1,6]. Lymph nodes, liver, lung, bone, and peritoneum are the most common metastatic sites of urothelial carcinoma of bladder, whereas skin, brain, heart, and kidney are rarely involved [1-3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations